Assessing School Managers Occupational Stress and Coping Strategies: Their Influence on Managerial Competence - Magalona, Jason D.; Manzano, Eddie C. (Journal of Ecohumanism, 2024)
Occupational stress is a pervasive concern across various professions, significantly impacting individuals' well-being and job performance. In the educational sector, school managers, including principals, head teachers, and teachers-in-charge, face unique challenges that contribute to high levels of stress and lead to unfavorable working conditions and significant occupational stress. The study aimed to examine the level of occupational stress experienced by school managers in Guiuan, Eastern Samar, identify their coping strategies, and assess how these factors influence their managerial competence. A purposive sampling technique was used to select participants who could provide the most relevant information for the study's objectives. It employed a descriptive correlational survey design to assess the relationship between occupational stress, coping strategies, and managerial competence among school managers in Guiuan. The respondents include 48 school managers from three school districts within Guiuan. Findings revealed that school managers in Guiuan experience high levels of occupational stress due to factors such as poor working environments, curriculum implementation challenges, and economic issues. Effective coping strategies identified include delegation of duties, developing close staff relationships, and practicing good time management. Furthermore, a significant majority of school managers demonstrate outstanding managerial competence, indicating strong leadership abilities despite the high levels of stress. It concluded that while school managers in Guiuan face significant occupational stress, they employ commendable coping strategies and exhibit high levels of managerial competence. The importance of addressing occupational stress and supporting school managers in Guiuan, Eastern Samar, through targeted interventions and policies aimed at enhancing their coping strategies and managerial competence.